Evaluation of invitro Antioxidant Activity of Artocarpus altilis (Parkinson) Fosberg (International Journal of Food and Nutritional Sciences, 2022)
Introduction: Antioxidants play a crucial role to protect the damage caused by oxidative stress (OS) in living cells. Plants having different metabolites were reported to possess antioxidant as well as anticancer properties. The present investigation dealt with the analysis of antioxidant properties of crude solvent extracts of matured unripe seedless fruits of Artocarpus altilis (Parkinson) Fosberg (commonly known as breadfruit) under in vitro condition. Methods: The antioxidant activities of fruit extracts were evaluated in vitro using standard method such as DPPH (1,1-diphenyl-2picrylhydrazine) radical scavenging assay, hydroxyl radical scavenging assay, ferrous reducing antioxidant capacity, phosphomolybdnum assay, nitric oxide radical scavenging assay, superoxide radical scavenging assay, hydrogen peroxide radical scavenging assay using ascorbic acid as standard.Results: All the assays conducted with methanolic breadfruit extracts revealed the free radical scavenging capacity with nitric oxide radical scavenging assay as the better one. Conclusion: The results revealed the efficiency of breadfruit as a potent biological antioxidant agent.